Study Quality in Quantitative L2 Research: A Path Analysis on the Perceptions of Iranian Published Authors - Parviz Ajideh; Mohammad Zohrabi; Akbar Jahanbakhsh (Journal of Modern Research in English Language Studies)
Inspired by the works of scholars who have done great efforts to improve study quality in second language (L2) papers in the recent decade (e.g., Hu & Plonsky, 2019; Larson-Hall, 2012, 2017; Plonsky, 2013; Norris, 2015), this paper aims to capture the perceptions of Iranian authors around issues of quality that have been emphasized by publication manuals (e.g., APA, 2010; Wilkinson, 1999) and recommendation (e.g., Norris et al., 2015). The triggering idea behind the study was that in order to adhere to standards of quality, authors, first, need to perceive the issues highly-associated with the concept. Accordingly, a questionnaire of quality developed by  Larson-Hall and Jahanbakhsh (in review) was used to capture respondents’ perceptions. Out of the 1029 authors who had published quantitative papers in 10 Iranian journals from 2015 to 2019, 885 authors could be contacted and 128 answered the questionnaire. The results showed that respondents saw fundamental issues like random sampling, reliability, validity, checking normality, and reporting inferential statistics as the most highly-associated features with quality while the concerned issues by scholars, like generalizability in convenience samplings, use of delayed posttest, reporting non-significant results, and importance of visual presentations are less acknowledged. Moreover, using Structural Equation Modeling (SEM), it was revealed that a path of perception exists which starts from sampling issues and going through design and statistical to reporting practices. It was recommended that authors take the issues of study quality more seriously in both their works and the context of education.